Penyuluhan dan Pelatihan: Menumbuh Kembangkan Karakter Kewirausahaan dengan Memanfaatkan Media Digitalisasi - Yusrita; Lusi Elviani Rangkuti; Julienda Br. Harahap; M. Prasetyo Wibowo; Muhammad Joni Barus (Jurnal SOLMA, 2023)
Background: Entrepreneurship is one way to increase income for the community and open up jobs for yourself and also for others so that we will reduce the number of unemployed. Almost most of the residents are fishermen, and farmers have the opportunity to use the results of catches to be made into products produced from fish, shrimp and others, besides that there is a program to support entrepreneurship carried out by the new market village community with village funds, they managed into Bumdes. With the opportunity but not yet utilized by the community, UISU Economics Lecturers and Students carry out Community Service activities to grow and develop entrepreneurial character by utilizing digitalization media for the Pasar Baru Village, Teluk community Mengkudu District, Deli Serdang Regency. This activity was carried out at the village head's office, attended by the people of Pasar Baru Village, Teluk Mengkudu District, and Deli Serdang District, especially homemakers. Method: the implementation of this service is carried out through counseling and training through lectures, discussions, and questions and answers to service participants of Pasar Baru Village, Teluk Mengkudu District, Serdang Bedagai Regency. Results: Service participants understand utilizing existing resources in Pasar Baru Village by building community character in developing entrepreneurial spirit and using the currently developing digital media and social media. Conclusion: Villagers who participate in this service and have high motivation in entrepreneurship can create and produce productive and creative value from their natural resources and understand utilizing digitalization media as a marketing forum in entrepreneurship.